Harmful or Beneficial to Humans and the Environment? An Empirical Study on the Social Acceptance and Risk Perception of CO2-Based Fuels - Linzenich, Anika; Engelmann, Linda; Arning, Katrin; Du, Miaomiao; Heger, Sebastian; Roß-Nickoll, Martina; Ziefle, Martina (Frontiers in Environmental Science, 2022)
Risk analysis and assessment of toxic effects are important elements to be considered in the development of renewable fuels, such as CO2-based fuels made from CO2, water, and renewable energy. However, the successful introduction of CO2-based fuels could also be affected by public concerns about possible risks and adverse effects on health and the environment. In order to examine risk perceptions of laypeople in for CO2-based fuels and to understand if they can act as a barrier for the public acceptance of these fuels, we carried out an online survey with German laypeople. A special focus was placed on perceptions of toxic effects such as beliefs about exposure pathways and resulting health impacts, but also on participants’ openness towards CO2-based fuels. Results showed that CO2-based fuels were seen as an acceptable and beneficial technology and risks were perceived to be low. By tendency, lower risk perceptions were related to a higher acceptance of CO2-based fuels. The overall risk judgment was impacted by fears about toxic effects, concerns about environmental pollution, and the perceived general harmfulness of CO2-based fuels. The general openness towards CO2-based fuels was revealed to affect risk perceptions and beliefs about toxic effects: A higher openness towards the topic was linked to less severe concerns about CO2-based fuels. The findings from this study provide valuable insights on how to develop communications concepts to inform laypeople about possible risks and benefits of CO2-based fuels to address their concerns and information demands and give them a better understanding for the effects of toxic substances on different risk targets.